A SYSTEMATIC REVIEW OF THE STUDIES ON THE GOD IMAGE IN THE SAMPLE OF TÜRKİYE - Özlem Güler Aydın (Dini Araştırmalar)

(untitled)
The objective of this article is to conduct a systematic review of empirical research focused on the concept of God image within the context of Türkiye. The multidimensional nature of the God image is explored, and its associations with various variables, encompassing sociodemographic and psychological aspects, are thoroughly examined. The review also considers the correlation between God image and psychopathology, as well as spiritual care. The findings from this review, specific to the Turkish sample, suggest that the God image doesn't consistently vary with age, but a positive relationship is evident, indicating a tendency for a more positive God image with age. Women tend to have a more love-oriented God image than men. However, no significant distinctions were found in terms of income and educational levels. Moreover, variations of God image may be influenced by the type of school (religious or secular) and parental attitudes. Studies suggest that individuals raised in environments characterized by oppressive, authoritarian, or neglectful parenting are prone to form fear-oriented God images, while those with democratic parenting tend toward love-oriented God images. Subjective religiosity and positive religious coping are also proposed to have a positive correlation with the perception of God. Alongside sociodemographic variables, it is argued that a more positive and love-oriented God image is positively associated with enhanced psychological health, greater well-being, effective coping, positive self-esteem, lower depression, and fewer psychopathological symptoms. Despite the insights from the review of 55 studies, the diversity of examined variables necessitates more extensive research to draw general conclusions for each variable within the Turkish sample. Finally, fields requiring further investigation were also identified.